(untitled) (Ameghiniana, 2013)
The xylem structure of a possible silicified fossil root from the Río Turbio Formation, Santa Cruz Province, was studied. Stratigraphic data suggest that the plant bearing bed is Eocenein age. The xylem has two ray types: broad and 1-2 seriate. Vessels are disposed in tangencial series and the paratracheal parenchyma is scarce. The structure and composition of the wall of all xyleme elements were modified during fossilization. The marerilal was analysed with U.V., P.L. and microchemical reactives. The absence of central medulla and the presence of fragmentary primary xylem instead suggest that the fossil is a root and not a stem.